Surgery A Case Based Clinical Review - de Virgilio, Christian; Frank, Paul N.; Grigorian, Areg (Springer New York : Imprint: Springer, 2015)
Surgery: A Case Based Clinical Review provides the reader with a comprehensive understanding of surgical diseases in one easy-to-use reference that combines multiple teaching formats. The book begins using a case based approach. The cases presented cover the diseases most commonly encountered on a surgical rotation. The cases are followed by a series of short questions and answers, designed to provide further understanding of the important aspects of the history, physical examination, differential diagnosis, diagnostic work-up and management, and questions that may arise on surgical rounds. Key figures and tables visually reinforce the important elements of the disease process.   Surgery: A Case Based Clinical Review will be of great utility for medical students when they rotate on surgery, interns, physician assistant students, nursing students, and nurse practitioner students.